AB0128 Alterations of the splicing machinery components in leukocytes from patients with systemic lupus erythematosus influences its development and atherothrombotic profile and drives the therapeutic response. (15th June 2017) - Perez-Sanchez, C; Aguirre, MA; Pedraza-Arévalo, S; del, M Río-Moreno; Ruiz-Limόn, P; Barbarroja, N; Jimenez-Gomez, Y; Rosa, I Arias-de la; Abalos-Aguilera, MC; Segui, P; Collantes, E; Castaño, J; et al.
Abstract : Background: Recent studies emphasize the relevance of alternative splicing in the development of genetic and autoimmune diseases and suggest therapeutic possibilities based on the modulation of this process. Objectives: To identify alterations in the leukocyte splicing machinery of patients with systemic lupus erythematosus (SLE) and to evaluate its influence on the development and activity of the disease, its atherothrombotic profile, and the response to specific therapies. Methods: An array of selected components of the major-(n=12) and minor-spliceosome (n=4) and associated splicing factors (n=28) was developed, and their expression levels were evaluated using a Fluidigm methodology, in purified leukocytes from 36 SLE patients and 29 healthy donors (HD). In parallel, an extensive clinical/serological evaluation was performed. Carotid intimate media thickness (CIMT) was used as atherosclerosis marker. Endothelial activity was monitored by laser-doppler, and pro-inflammatory and oxidative stress markers were quantified by flow cytometry and RT-PCR. In a parallel cohort of SLE patients (n=12), the effects of in vivo treatment with ubiquinol on spliceosome components was evaluated. Results: As a general feature, a significant reduction in splicing factors and spliceosome components was found in all the leukocytes of SLE patients. Interestingly, we found a specific altered profile of splicing factors and spliceosome components when compared monocytes (U2AF1, FBP11, SRSF9), lymphocytes (RBM22, PRP8, SRSF5) and neutrophils (RNU4, CA150). The reduced levels of some components of spliceosome in both monocytes and neutrophils were linked to the occurrence of thrombotic events, foetal loss and arterial hypertension. In lymphocytes, those reduced levels were strongly related to the positivity for anti-dsDNA antibodies in SLE patients, thus suggesting that reduced spliceosome machinery would contribute to increase in altered autoantigen assembly, inducing increased autoantibody production. Correlation studies demonstrated an inverse relationship among reduced levels of spliceosome components/splicing factors and high activity of the disease (measured as SLEDAI), endothelial dysfunction, and increased expression levels of peroxides and peroxynitrites, as well as of altered mitochondrial membrane potential in monocytes and neutrophils. In vitro treatment of leukocytes from HDs with anti-dsDNA promoted a reduction in spliceosome components associated with the expression of proinflammatory and oxidative mediators. Finally, in vivo treatment with ubiquinol reversed reduced expression in SLE of spliceosome components related to their proaterothrombotic profile. Conclusions: These results reveal the existence of SLE- associated spliceosome alterations -promoted by anti-dsDNA antibodies-which could be related to the development and activity of this autoimmune condition and have influence on the induction of mechanisms that drive atherothrombosis as well as the therapeutic response. Acknowledgements: Funded by CTS7940 and ISCIII (PI15/01333 and RIER RD16/0012/0015). Disclosure of Interest: None declared